Thada Is Dispensable for Female Fertility in Mice - Han, Shan; Zhang, Yuqing; Zheng, Yukun; Liu, Congcong; Jiang, Yonghui; Zhao, Shigang; Zhao, Han (Frontiers in Endocrinology, 2022)
Genome-wide association studies (GWAS) have identified THADA as one of the susceptibility genes for polycystic ovary syndrome (PCOS). Single nucleotide polymorphisms (SNPs) in the THADA gene showed significant over-transmission in PCOS and strong correlations with testosterone level. However, there was insufficient evidence to verify the effect of THADA in vivo on the female reproductive system. In this study, we investigated the impacts of Thada ablation on ovarian function and reproductive outcomes with knockout (KO) mice. The results showed that the Thada deletion was insufficient to affect ovarian folliculogenesis, steroidogenesis, and female fertility. Additionally, we stressed the mice with a high-fat-high-sugar diet (HFHS). In this case, the KO mice still merely had a negligible impact on ovarian function. These findings indicated that Thada deficiency was dispensable for female fertility in mice, which enriched our knowledge about in vivo functions of PCOS susceptibility genes.